2019
DOI: 10.1242/jcs.227660
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function analysis of the C. elegans aminophospholipid translocase TAT–1

Abstract: The Caenorhabditis elegans aminophospholipid translocase TAT-1 maintains phosphatidylserine (PS) asymmetry in the plasma membrane and regulates endocytic transport. Despite these important functions, the structure-function relationship of this protein is poorly understood. Taking advantage of the tat-1 mutations identified by the C. elegans million mutation project, we investigated the effects of 16 single amino acid substitutions on the two functions of the TAT-1 protein. Two substitutions that alter a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…5 B). This frequency is higher than the value of approximately 8% reported by other groups that introduced hundreds of small mutations per strain 14 , suggesting that the introduction of deletion variants by TMP/UV more efficiently produced mutations affecting the protein-coding genes. Furthermore, we also annotated the variants in intergenic regions, and we found that more than half of them were located in areas annotated with enhancers, promoters, and transcription factor binding regions 43 that could be involved in transcriptional regulation (Fig.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…5 B). This frequency is higher than the value of approximately 8% reported by other groups that introduced hundreds of small mutations per strain 14 , suggesting that the introduction of deletion variants by TMP/UV more efficiently produced mutations affecting the protein-coding genes. Furthermore, we also annotated the variants in intergenic regions, and we found that more than half of them were located in areas annotated with enhancers, promoters, and transcription factor binding regions 43 that could be involved in transcriptional regulation (Fig.…”
Section: Resultscontrasting
confidence: 65%
“…Another group reported an alternative approach 13 to introduce high-density point mutations and small indels per line using DNA alkylation agents such as EMS and ENU. However, it has been reported that point mutations rarely show a phenotype, except for those causing amino acid variations within important motifs 14 . Also, although high-frequency mutations are suitable for forward genetic screening, they are not a suitable approach for functional analysis of individual genes because of the effort required to isolate individual mutations.Therefore, to efficiently construct mutant libraries for the analysis of individual gene functions, it is important to establish methods for the generation of organisms with mutations that can be easily genotyped with high frequency to the extent that they can be isolated by crossing.…”
Section: Introductionmentioning
confidence: 99%
“…PS is one of the phospholipids distributed asymmetrically on the cell membrane. PS is almost only located in the inner leaf of the plasma membrane . However, in apoptotic cells, PS will turn from the inner leaf to the outer leaf of the plasma membrane and be exposed to the external environment of cells.…”
Section: Discussionmentioning
confidence: 99%
“…PS is almost only located in the inner leaf of the plasma membrane. 38 However, in apoptotic cells, PS will turn from the inner leaf to the outer leaf of the plasma membrane and be exposed to the external environment of cells. Studies have shown that PS eversion plays an important role in CaOx urolithiasis caused by hyperoxaluria.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, tat-1 mutants can also accumulate large endolysosomal vacuoles with PS externalization in the intestine suggesting that maintenance of PS asymmetry plays a role not only in apoptosis, but also endosomal trafficking [ 104 , 105 ]. Though the mechanism of this process is still poorly understood, a recent analysis of C. elegans mutants from the million mutants project identified specific motifs of TAT-1, PISL and DKTGT that play a functional role in the flippase activity, and that these domains are conserved in mammalian systems [ 106 ]. Finally, TAT-1 activity is controlled by PSR-1/JMJD6 and CED-1/LRP1 as loss of function mutants of either of these receptors lead to unengulfed PS externalized living cells [ 107 , 108 ].…”
Section: Apoptosismentioning
confidence: 99%